Tingkat Kepuasan Pasien BPJS Di Tempat Pendaftaran Pasien Rawat Jalan Di Rumah Sakit Hermina Bitung Kabupaten Tanggerang - Angelina Angelina; Lily Widjaja; Nanda Aula Rumana; Puteri Fannya (Pusat Riset dan Inovasi Nasional, 2024)
Patient satisfaction is a factor that can be used as a reference in determining the success of a service program. Patient satisfaction will arise when it is supported by good quality service. There are five dimensional aspects known as service quality (SERVQUAL), reliability, responsiveness, assurance, empathy, and tangible. These five dimensions influence patient satisfaction. This research aims to provide an overview of the level of satisfaction of outpatient BPJS patients at Hermina Bitung Hospital, Tanggerang Regency in 2023. This research uses a descriptive method with a quantitative approach with the data that has been collected being processed using SPSS (statistical packagen for the social sciences) then the results analyzed by measuring the average percentage for each patient criterion and a sample size of 76 respondents, from this research it can be concluded that patient satisfaction through the reliability dimension is 56.58%, the responsiveness dimension is 55.26%, the assurance dimension was 53.95%, the empathy dimension was 56.58%, while the direct evidence (tangible) was 51.32%. Thus, the researchers concluded that the number of BPJS patients in outpatient registration services was 52.63%. This result still does not reach the minimum service standard set by the Indonesian Ministry of Health in 2008, which is ≥90%.